The Impact of Coffee Price Fluctuations on Demand in Rejang Lebong District - Agustina, Rani Ade; Silamat, Eddy; Prisdinawati, Dwita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted in April 2025 to Mid-May 2025. This study aims to: Analyze the impact of coffee price fluctuations on demand in Rejang Lebong. Determination of respondents in this study using the Accidental sampling method. The method used in this study is Quantitative. The results of this study are that the impact of coffee price fluctuations on coffee demand in Rejang Lebong Regency is that there is an influence of the impact of coffee price fluctuations on coffee demand in Rejang Lebong Regency, especially in Selupu Rejang District, with an amount of 13.1%. The results of the simple linear regression analysis show that the Coffee Price Fluctuation value is constant or remains at 30,418. and the value of the regression direction coefficient/b (X) is 0.515 which is positive, meaning that coffee price fluctuations increase by one (1) unit, then demand will increase by 0.515. So there is a Significance value of the Fluctuation Variable of 2,050> 1,703 So Ha is accepted and Ho is rejected, meaning that the coffee price fluctuation variable has an effect on demand in Rejang Lebong Regency, especially in Selupu Rejang District.